The Effect of 5E Inquiry Learning Model on the Science Achievement in the Learning of Ã¢â‚¬Å“MagnetÃ¢â‚¬Â among Year 3 Students - Ong, E. T.; Keok, B. L.; Yingprayoon, J.; Singh, C. K.S.; Borhan, M. T.; Tho, S. W. (Jurnal Pendidikan IPA Indonesia, 2020)
The aim of this study is to determine the effect of the 5E Inquiry Learning Model as compared to the conventional method in enhancing third-grade studentsÃ¢â‚¬â„¢ science achievement using Ã¢â‚¬Å“magnetÃ¢â‚¬Â as the learning material. A quasi-experimental pretest-posttest control group design was employed with the participation of 40 students from two intact Third-grade classes in a primary school in Kuala Kangsar. The experimental group was taught using the 5E Inquiry Learning Model which consists of 5 stages, namely Engagement, Exploration, Explanation, Expansion, & Evaluation, while the control group was taught using the teacher-centered conventional method. The science achievement in the learning of Ã¢â‚¬Å“MagnetÃ¢â‚¬Â was measured using a researcher-developed test consisting of 12 multiple-choice and 8 fill-in-the-blank items. The test has sufficient validity and KR-20 reliability. Analysis of the pretest data indicates that there was no statistically significant difference (t = 1.66, p > .05) in the pretest means between the experimental and control groups. Accordingly, an independent samples t-test was used to compare studentsÃ¢â‚¬â„¢ achievement in the posttest. The analysis of the posttest data indicates that the posttest mean in science achievement (16.05) among the group of students who had followed through the 5E Inquiry Learning Model is statistically significantly higher (t = 4.75, p < .001) than the corresponding mean (13.15) among the group of students in the control group. Therefore, it can be concluded that the 5E Inquiry Learning Model enhances the learning of science in terms of achievement among the primary students.Ã‚Â Ã‚Â